RISK MANAGEMENT RELATED TO IDENTIFYING WORK ACCIDENTS IN LOADING AND UNLOADING CONTAINER ACTIVITIES AT THE BERLIAN TERMINAL TANJUNG PERAK SURABAYA WITH THE HAZARD IDENTIFICATION RISK ASSESSMENT AND DETERMINING CONTROL (HIRADC) METHOD - Alfri Yoga Kurniawan; Fredy Kurniawan (NAROTAMA UNIVERSITY, Indonesia, 2020)
The Berlian Terminal is one of the container terminals located in the Port of Tanjung Perak Surabaya, managed by PT BJTI PORT. Container loading and unloading activities have a risk of work accidents. Work accidents can be prevented by applying Hazard Identification, Risk Assessment, and Determining Control (HIRADC). HIRADC aims to identify potential hazards in the workplace by linking workers, tasks, work equipment, and the work environment. This study aims to determine the application of HIRADC to reduce the risk of accidents. This type of research is descriptive research. The total sample of 52 workers, taken by the total sampling method. Data related to respondent characteristics such as worker productivity and the OHS Program on HIRADC were obtained by direct observation in the field and interviews with all workers. The results showed that workers who had high productivity were (71.1%). Statistical tests using the ordinal regression test showed that there was an influence between the OHS Program on HIRADC and the Productivity of Work for Workers in Berlian Terminal (0,000 <0.05). The implementation of the OHS Program at the Berlian Terminal is good and needs to be maintained, if possible, it can be improved by increasing the competency of OHS Supervisors and OHS management following OHS regulations.